2021
DOI: 10.3390/ijms221910723
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively Activating Mutants of Equine LH/CGR Constitutively Induce Signal Transduction and Inactivating Mutations Impair Biological Activity and Cell-Surface Receptor Loss In Vitro

Abstract: The signal transduction of the equine lutropin/choriogonadotropin receptor (eLH/CGR) is unclear in naturally occurring activating/inactivating mutants of this receptor, which plays an important role in reproductive physiology. We undertook the present study to determine whether conserved structurally related mutations in eLH/CGR exhibit similar mechanisms of signal transduction. We constructed four constitutively activating mutants (M398T, L457R, D564G, and D578Y) and three inactivating mutants (D405N, R464H, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 44 publications
2
15
1
Order By: Relevance
“…This phenomenon, known as desensitization, is caused by factors that regulate the quantity of the hormone receptor [ 2 ]. The receptors occupied by the agonist respond to the G protein stimulator (Gs), which, in turn, activates adenylyl cyclase, resulting an in increased synthesis of cyclic adenosine monophosphate (cAMP) through the protein kinase A pathway (PKA) [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon, known as desensitization, is caused by factors that regulate the quantity of the hormone receptor [ 2 ]. The receptors occupied by the agonist respond to the G protein stimulator (Gs), which, in turn, activates adenylyl cyclase, resulting an in increased synthesis of cyclic adenosine monophosphate (cAMP) through the protein kinase A pathway (PKA) [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have studied the GPCR signal transduction of activating and inactivating lutropin/chorionic gonadotropin receptors (LH/CG) and FSHRs, showing that the highly conserved regions in glycoprotein hormone receptors are similarly regulated in different species of both mammals and fish [ 3 , 4 , 5 ]. In recent years, we have been studying signal transduction in activating and inactivating mutants to characterize the specific function of the PKA pathway [ 17 ] and cell-surface loss of receptors [ 18 ] in eel LH/CGR.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the five-day treatment with TP3 did not significantly affect the LH/hCG-R expression, and, as a result, the TP3 effect on the testosterone level did not change significantly during all days of treatment ( Figure 2 ). The other authors showed that hyperactivation of LH/hCG-R with chronic administration of gonadotropin leads to desensitization and down-regulation of the receptor [ 72 , 73 , 74 , 75 , 76 ], and in addition to this, the increased testosterone levels through a negative feedback mechanism suppress the expression of the Lhr gene [ 74 ]. According to our early data, treatment of rats with TP4/2, another allosteric LH/hCG-R-agonist, had a little effect on the Lhr expression [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…cAMP accumulation in the CHO-K1 cells and PathHunter Parental cells expressing eLH/ CGR-wt and eLH/CGR-t656 mutants was measured using cAMP Dynamics 2 competitive immunoassay kits as described previously ( Byambaragchaa et al, 2021e ). The cAMP response assay used a cryptate-conjugated anti-cAMP monoclonal antibody and a d2-labeled cAMP reagent.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the C-terminal region of eLH/CGR has 14 potential phosphorylation sites and a highly conserved leucine motif that is essential for trafficking ( Duvernay et al, 2004 ; Byambaragchaa et al, 2021a , b , e ). The eCG, secreted from the placenta during early pregnancy, is a unique molecule that displays both LH- and FSH-like activities in non-equid species ( Min et al., 2019 , 2020 , 2021 ; Lee et al, 2021 ) and exhibits only LH-like activity in equine species ( Lee et al, 2017 , 2021 ; Park et al, 2017 ; Min et al, 2019 , 2020 ; Byambaragchaa et al, 2021c , d ).…”
Section: Introductionmentioning
confidence: 99%